njury rate and risk factors among small scale gold miners in Ghana - Nakua Kweku Emmanuel; Owusu-Dabo Ellis; Newton Samuel; Koranteng Adofo; Otupiri Easmon; Donkor Peter; Mock Charles (BioMed Central, 2023)
This article is published by BioMed Central and is also available at https://doi.org/10.1186/s12889-019-7560-0